Valproic acid restricts mast cell activation by Listeria monocytogenes - Rodolfo Soria-Castro; Yatsiri G. Meneses-Preza; Gloria M. Rodríguez-López; Alfredo Ibarra-Sánchez; Claudia González-Espinosa; Sonia M. Pérez-Tapia; Fabián Flores-Borja; Sergio Estrada-Parra; Alma D. Chávez-Blanco; Rommel Chacón-Salinas (Scientific Reports, 2022)
Abstract Mast cells (MC) play a central role in the early containment of bacterial infections, such as that caused by Listeria monocytogenes (L.m). The mechanisms of MC activation induced by L.m infection are well known, so it is possible to evaluate whether they are susceptible to targeting and modulation by different drugs. Recent evidence indicates that valproic acid (VPA) inhibits the immune response which favors L.m pathogenesis in vivo. Herein, we examined the immunomodulatory effect of VPA on L.m-mediated MC activation. To this end, bone marrow-derived mast cells (BMMC) were pre-incubated with VPA and then stimulated with L.m. We found that VPA reduced MC degranulation and cytokine release induced by L.m. MC activation during L.m infection relies on Toll-Like Receptor 2 (TLR2) engagement, however VPA treatment did not affect MC TLR2 cell surface expression. Moreover, VPA was able to decrease MC activation by the classic TLR2 ligands, peptidoglycan and lipopeptide Pam3CSK4. VPA also reduced cytokine production in response to Listeriolysin O (LLO), which activates MC by a TLR2-independent mechanism. In addition, VPA decreased the activation of critical events on MC signaling cascades, such as the increase on intracellular Ca2+ and phosphorylation of p38, ERK1/2 and -p65 subunit of NF-κB. Altogether, our data demonstrate that VPA affects key cell signaling events that regulate MC activation following L.m infection. These results indicate that VPA can modulate the functional activity of different immune cells that participate in the control of L.m infection.